Quercetin Liposomal Nanoformulation for Ischemia and Reperfusion Injury Treatment - Margarida Ferreira-Silva; Catarina Faria-Silva; Manuela C. Carvalheiro; Sandra Simões; H. Susana Marinho; Paulo Marcelino; Maria Celeste Campos; Josbert M. Metselaar; Eduarda Fernandes; Pedro V. Baptista; Alexandra R. Fernandes; Maria Luísa Corvo (MDPI AG, 2022)
Ischemia and reperfusion injury (IRI) is a common complication caused by inflammation and oxidative stress resulting from liver surgery. Current therapeutic strategies do not present the desirable efficacy, and severe side effects can occur. To overcome these drawbacks, new therapeutic alternatives are necessary. Drug delivery nanosystems have been explored due to their capacity to improve the therapeutic index of conventional drugs. Within nanocarriers, liposomes are one of the most successful, with several formulations currently in the market. As improved therapeutic outcomes have been demonstrated by using liposomes as drug carriers, this nanosystem was used to deliver quercetin, a flavonoid with anti-inflammatory and antioxidant properties, in hepatic IRI treatment. In the present work, a stable quercetin liposomal formulation was developed and characterized. Additionally, an in vitro model of ischemia and reperfusion was developed with a hypoxia chamber, where the anti-inflammatory potential of liposomal quercetin was evaluated, revealing the downregulation of pro-inflammatory markers. The anti-inflammatory effect of quercetin liposomes was also assessed in vivo in a rat model of hepatic IRI, in which a decrease in inflammation markers and enhanced recovery were observed. These results demonstrate that quercetin liposomes may provide a significant tool for addressing the current bottlenecks in hepatic IRI treatment.